Home time. Book two, Beyond the weaving - Whyte, Campbell, 1984- (Top Shelf Productions, 2020)
Lost, scared, confused, even burnt, six young friends are trapped in a fantasy world of fruit-creatures and lizard-folks, and just want to find a way home. Leaving Peach Village, searching for answers, medicine, and a way home, Lily, Amanda, Nathan, Ben, and their companions have a plan so stupid it just might work.